Democratization as the instrument of realization of the USA foreign policy interests in Central Asia (International relations and international law Journal, 2018)
The article is focused on the influence of the United States of America on the region of Central Asia in accordance with a modern international situation. The Central Asian countries are expected as the attractive region for world powers. The main stages of interaction with the region and transformation of strategic interests in Central Asia were revealed. According to the international situation they evolved and captured cooperation in such spheres as economic integration, military cooperation, security, cultural exchange, education, protection of human rights. The author considers democratization as the main and integral tool in implementation of a foreign policy of USA in the context of its global strategy. The author analyzes problem aspects and features of democratic processes in Central Asia, and also reveals methods which are applied by Washington to effective realization of its external course. In addition, the presented statistics by which the assessment of the work carried out in the region, and recommendations for further development of democracy in the states of Central Asia are output.Key words: democratization, geostrategy, transformation, rating, non-governmental organizations, integration, financing, legal regulation.